2013
DOI: 10.1016/j.jacc.2012.11.060
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Yoga on Arrhythmia Burden, Anxiety, Depression, and Quality of Life in Paroxysmal Atrial Fibrillation

Abstract: In patients with paroxysmal AF, yoga improves symptoms, arrhythmia burden, heart rate, blood pressure, anxiety and depression scores, and several domains of QoL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
133
1
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(142 citation statements)
references
References 11 publications
2
133
1
6
Order By: Relevance
“…It has been previously suggested that personal psychology and presence of psychological distress might, through an influence on the sympathetic nervous system, systemic and regional inflammation, and endothelial function, be factors contributing to AF development,24 and it is likely that psychological factors and a distressed personality would increase the likelihood of detecting AF episodes. A personality marked by chronic tension has been associated with increased risk of incident AF in men,25 the Type D Personality has specifically been associated with an increased risk of incident AF following cardiac surgery,26 depression is associated with increased risk of recurrent AF after electrical cardioversion and catheter ablation,27 and yoga has been demonstrated not only to improve hrQOL and reduce psychological distress in AF, but also even to reduce the frequency of symptomatic and asymptomatic AF episodes recorded by external monitoring 24.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been previously suggested that personal psychology and presence of psychological distress might, through an influence on the sympathetic nervous system, systemic and regional inflammation, and endothelial function, be factors contributing to AF development,24 and it is likely that psychological factors and a distressed personality would increase the likelihood of detecting AF episodes. A personality marked by chronic tension has been associated with increased risk of incident AF in men,25 the Type D Personality has specifically been associated with an increased risk of incident AF following cardiac surgery,26 depression is associated with increased risk of recurrent AF after electrical cardioversion and catheter ablation,27 and yoga has been demonstrated not only to improve hrQOL and reduce psychological distress in AF, but also even to reduce the frequency of symptomatic and asymptomatic AF episodes recorded by external monitoring 24.…”
Section: Discussionmentioning
confidence: 99%
“…A personality marked by chronic tension has been associated with increased risk of incident AF in men,25 the Type D Personality has specifically been associated with an increased risk of incident AF following cardiac surgery,26 depression is associated with increased risk of recurrent AF after electrical cardioversion and catheter ablation,27 and yoga has been demonstrated not only to improve hrQOL and reduce psychological distress in AF, but also even to reduce the frequency of symptomatic and asymptomatic AF episodes recorded by external monitoring 24. Neurohormonal activation and inflammation certainly play a role in atrial remodeling in AF,28 and chronic stress may activate such physiological systems 29.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from these findings, it has been well documented through previous psycho-physiological research carried out in our research laboratories suggest that Cyclic meditation, which is a key component of SMET could produce positive impact on attention [23], slow wave sleep (quality of sleep) [24] in healthy volunteers and physiological stress [25] in corporate leaders. Yoga has already been considered an effective intervention found to reduce the anxiety [26] and stress [27] and as stress reduces the leadership abilities by increasing the amount of diurnal cortisol [28]. Hence SMET would have produced a noticeable change in the MLQ scores of the leaders.…”
Section: Discussionmentioning
confidence: 99%
“…In a study in Bombay, the shavasana group had a significant decrease in blood pressure [19]. Yogic practices have been shown to have significant benefits for cardiovascular health: through these practices heart rate, systolic blood pressure and diastolic blood pressure decrease significantly [20][21][22]. In another study it was observed that after fast pranayama basal heart rate was reduced [23].…”
Section: Discussionmentioning
confidence: 99%